Rancang Bangun Aplikasi Distribusi Dan Penanganan Keluhan Pada Universitas Banten Jaya - Qurohman, Tauffik; Romdoni, Mochamad Yusuf; Fatoni, Ahmad; Fatullah, Rizki; Shavira, Adinda (Jurnal Ilmiah Sains dan Teknologi, 2024)
Research to analyze the student complaint service system at Banten Jaya University so that it can be more effective in accepting and serving students for the advancement of the academic community on campus. Complaints and consultations are the process of conveying information, aspirations and complaints, whether complaints regarding the lack of campus academic services, regarding learning activities and so on. At Banten Jaya University the process of handling complaints and grievances is still done manually and the complaint data has not been computerized. So there is a lack of information regarding the complaint handling process that can be known by the consultant. The aim of this research is to design the UNBAJA Peduli (SIJALI) Application to assist in distribution and complaint handling services at Banten Jaya University. This application is designed to be website-based so it can be accessed easily and uses the ILAD method as a problem solver.